KECENDRUNGAN MEDIA PEMBELAJARAN INTERAKTIF - Trimansyah Trimansyah (Fitrah, 2021)
This paper examines the tendency of interactive learning and how the steps are implemented to increase students' understanding of what is being studied, because the development of education in schools is growing day by day so that it undergoes changes, learning demands will always be adapted to these developments Therefore, the implementation of interactive learning is one way to make changes in the learning process. Interactivity is a characteristic of multimedia learning programs and the level of interactivity will determine how intense student involvement is in understanding learning, for conditions like this the presence of learning media is very useful, in such a position.